Intratumoral heterogeneity and potential treatment strategies in small cell lung cancer - Yang, Yunke; Liu, Nana; Wu, Jiaji; Wu, Qingzhe; Zhao, Jiangnan; Shi, Yue; Shen, Mo; Xu, Zhiyong; Shi, Yueli; Yu, Jianghao; Yi, Peng; Cheng, Jin; et al. (Frontiers in Oncology, 2025)
Small cell lung cancer (SCLC) is a highly aggressive malignancy characterized by early metastasis and poor prognosis due to the limited efficacy of current treatments. Although initially responsive to chemotherapy and radiotherapy, the majority of patients with SCLC develop resistance within a year, often succumbing to distant metastases. Historically, SCLC was considered a homogeneous disease, primarily driven by the deletion or inactivation of key tumor suppressor genes TP53 and RB1. However, recent advancements in genomics and single-cell sequencing have identified distinct molecular subtypes of SCLC, derived from studies on cell lines, animal models, and tumor tissues. The tumor’s complexity, marked by the coexistence of multiple dynamic subtypes, contributes to its pronounced heterogeneity. Notably, different subpopulations exhibit a complex spatial relationship characterized by both mutual exclusion and coexistence. Temporally, SCLC exhibits the ability to undergo subtype transformations through various molecular mechanisms, underscoring the tumor’s plasticity and offering novel perspectives for personalized treatment approaches. This review synthesizes recent discoveries regarding SCLC subtype classification, intratumor heterogeneity, plasticity-related signaling pathways, immune landscape, and emerging therapeutic strategies.